Strategi Guru dalam Mengatasi Tingkah Laku Negatif Anak Usia Dini di Taman Kanak-Kanak - Fanny Gistia Lestari; Thorik Aziz (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to analyze teachers' strategies in addressing negative behaviors among early childhood students in kindergarten settings. Negative behaviors in early childhood, such as fighting, taking others' belongings, and disobeying rules, have become an increasing problem in early childhood education institutions. These behaviors impact children's social-emotional development and learning effectiveness. This research is essential to identify effective strategies that teachers can apply to address such negative behaviors. The study was conducted at PKK Kartini Kindergarten using a descriptive qualitative approach. Data was collected through direct observation, interviews with 10 teachers, and a study of school policy documents. Data analysis was conducted thematically using NVivo software to identify main patterns and themes. The results show that teachers at PKK Kartini Kindergarten implement various strategies, including social and emotional skills development, group discussions, sharing exercises, and positive reinforcement. These approaches are supported by Bandura's social skills theory, Vygotsky's social development theory, Hirschi's social control theory, Skinner's positive reinforcement theory, and Erikson's emotional development theory. Although these strategies are effective, challenges include consistency in implementation and parental involvement. This study contributes to improving the quality of early childhood education by offering practical recommendations for addressing negative behaviors and creating a positive and productive learning environment.